Drone E-Job Sheet Development: Geospatial Engineering Remote Sensing Subject - Fadli, Azwar; Sitompul, Harun; Panjaitan, Keysar (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to produce an E-Job Sheet Drone Product for the Class XI Geospatial Engineering Remote Sensing Subject by carrying out feasibility tests, practicality tests, and product effectiveness tests. The research and development methodology uses the 4D development model (four-D models), namely definition, design, development, and dissemination, so that the development design is developed. This research was carried out at SMK Negeri 1 Percut Sei Tuan in class XI Geomatics Engineering in the Remote Sensing (Inderaja) subject. The research results show: (1) E-Jobsheet Drone, suitable for use in remote sensing learning for class XI at SMK Negeri 1 Percut Sei Tuan; (2) Drone E-Jobsheets have proven effective in improving student learning outcomes for class XI at SMK Negeri 1 Percut Sei Tuan compared to conventional learning methods. The application of learning media in the form of E-Jobsheet Drones requires students who are ready to learn independently so that they can achieve optimal learning outcomes by utilizing this media effectively